From one text to another (inOpera Esercizi di lettura su testi contemporanei, 2025)
The essay takes into consideration a poem by William Carlos Williams and the translation given by Vittorio Sereni, questioning the reasons for the affinities and differences existing between the two authors and what the ‘Italian’ text manages or fails to convey of the original: from the dark and bitter atmosphere of the first verses it finally turns to the recognition of how poetry has its roots linked to those of pain.
Keywords: Poem; Translation; Interpretation; William Carlos Williams; Vittorio Sereni